Assessing System Quality and Change Readiness in Enterprise Risk Management Application Adoption in Power Plants - Ambarwati, Rita; Hanifa, Muhammad; Dedy, Dedy; Sulistiyowati, Wiwik (Bina Nusantara University, 2024)
Real-time and accurate risk management data is critical in making informed corporate decision-making. An Enterprise Risk Management (ERM) application enhances data access speed and accuracy, supporting strategic actions. Developed with an integrated risk and technology management approach, this application aids in effective risk management in operational power plants facing complex, high-risk challenges. It offers a structured framework for identifying, assessing, and managing risks, ultimately enhancing operational efficiency, effectiveness, and safety. This research examined the impact of system quality and readiness to change on the perceived usefulness, perceived ease of use, and behavioralÂ intentions toward ERM applications. Data were gathered from 300 risk management professionals through purposive sampling. Then, the data were analyzed with PLS-SEM using a quantitative survey-based approach. The finding reveals that system quality and readiness to change significantly influence perceived usefulness and ease of use, which subsequently affect behavioral intentions. Interestingly, perceived usefulness does not directly impact behavioral intentions, emphasizing the critical roles of system quality and user readiness in ERM adoption. These finding underscores organizations' need to enhance the technical aspects of ERM applications and implement effective change management strategies to improve user engagement and adoption rates. The originality of this research resides in its integrated approach, merging system quality and readiness to change within the Technology, Acceptance, Model (TAM) framework, offering a deeper understanding of the factors driving ERM application acceptance. This research provides valuable insights for standardized frameworks, financial incentives, and tailored training programs to boost technology adoption.